Group cultural values and political skills: A situationist perspective on interpersonal citizenship behaviors - Mahajan, Ashish; Toh, Soo Min (Journal of International Business Studies, 2017)
Drawing on Mischel’s (1968) situationist perspective, we theorized that in a weak situation, one created by a group culture of low power distance (PD) or low uncertainty avoidance (UA), political skills increase the display of interpersonal citizenship behaviors. In a strong situation, one created by a high group PD or high group UA, the application of political skills is constrained. In a sample comprising of supervisor–employee groups from Canada and India, we highlight group culture as an important boundary condition on interpersonal citizenship behaviors and recommend that leaders carefully consider the cultures that they create in their groups.